Effect of Different Chemical Compounds and Nano-Formulations on the Cell Wall Components of Alternaria solani and A. alternata - Bhattacharjee, Jayashree; Bhattacharjee, Debashre; Basu, Amitava; Debnath, Chandan (Indian Journal of Hill Farming, 2019)
The effect of certain chemical compounds, i.e. chitosan nano-particle, silver nitrate, silver nano-particle, silvox, salicylic acid, hydrogen peroxide, titanium, titanium dioxide hydrophobic and hydrophillic nano-particle, silicon, silicon dioxide hydrophilic and lipophillic nano-particle in comparison with isoprothiolane (check fungicide), was assessed at 20 ppm on the glucose, protein, lipid contents of the mycelium of Alternaria solani and A. alternata which cause tremendous loses in potato cultivation through early blight. The isolation and identification of the pathogens, harvest of its mycelium and analysis was donefollowing standard protocols. There was a decrease in the level of glucose and protein and increase of lipid in the mycelium using the compounds. Nano-formulations were effective over conventional chemicals including check fungicide. Silver nano-particle was most effective amongst the nano- formulations and silver nitrate amongst the conventional chemicals. The efficacy of remaining compounds was better than check fungicide. From this, it was concluded that nano-particles and conventional chemical compounds can be used to replace synthetic fungicides to control the attacks of early blight through altering the cell wall components of the causative agents.